KUDETA JUNTA MILITER MYANMAR TERHADAP AUNG SAN SUU KYI 2021 - Willi Ashadi (Dauliyah Journal of Islamic and International Affairs, 2022)
This paper aims to find out and analyze how the coup carried out by the Myanmar military junta against Aung San Suu Kyi. This research began on November 8, 2022, the Government of Myanmar held a presidential election. The election was won by Aung San Suu Kyi through the National League Democracy (NLD) party. The election was won by Aung San Suu Kyi through the National League Democracy (NLD) party. The opposition through the Union Solidarity and Development did not recognize the election results. They claim that Aung San Suu Kyi's victory in Myanmar's election was carried out by fraud. This made the opposition party reject and the military junta supported the decision. Through the Myanmar military junta, Aung San Suu Kyi was arrested and the election was deemed invalid. The coup by the military junta against Aung San Suu Kyi was carried out so that Myanmar was declared a state of emergency after the military coup led by the military junta in Myanmar. Based on this the author tries to analyze how the military junta carried out a coup against Aung San Suu Kyi.